Leitura do gênero infográfico nas aulas de língua portuguesa: multimodalidade no ensino fundamental - Furtado, Rosilene Sabino (2020)
This study arose from the reading difficulties evidenced by students of the 9th grade of elementary school at a State School located in the city of Campina Grande / PB. It was noticed that the way reading has been worked in the classroom, does not arouse the interest of the student, which is confirmed in testimonies of teachers, especially those in Portuguese, when they state that students are not motivated to read and writing, when carrying out activities to meet the requirements of the discipline. Among these reading difficulties, there is the reading of graphs, which is fundamental for the understanding of a series of data in the current context and has not been given due importance in mother tongue classes. In line with this thought, it is interesting to guide the student to read different texts, with different objectives. For this, the infographic was chosen as a genre to be discussed because it is a multimodal text par excellence, considering its different modes of representation, articulating the verbal with the visual. The present study addressed the use of infographic in the classroom, not only as an instrument of social inclusion of the student as a subject in broader social practices, but also of teaching learning in the classroom by the teacher. Thus, the objective was to stimulate students' reading, integrating the non-verbal with the linguistic, through infographics. For the theoretical foundation, studies of Cairo (2008), Valero Sancho (2004), Ribeiro (2016), among others, were used. The study methodology proposed classroom intervention, articulated through an action research, after diagnostic activity, based on an ethnographic process with the active, dynamic and democratic participation of the subjects involved. The results showed that, initially, the students had minimal knowledge - not to say non-existent - about the infographic and what reading strategies they need to understand the multimodal text. With the intervention, the students' reading ability with regard to the infographic was developed and improved, although some continue to have reading difficulties. In this way, the relevance of a work with the reading of infographics is verified, either by the historical deficiency around reading in Brazil, or by the proximity of gender to the reality of students in contemporary society.